Evaluation of the Clinical Effectiveness of the Drug Laennec in Complex Rehabilitation of Patients with Post-COVID Syndrome: a Randomized Trial - Olga V. Yurova; Tatiana V. Konchugova; Tatiana V. Apkhanova; Ilmira R. Gilmutdinova; Valeriia A. Vasileva; Detelina B. Kulchitskaya; Larisa A. Marchenkova; Oleg S. Glazachev; Elena N. Dudnik; Maryana A. Ansokova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. The development of post-COVID syndrome is accompanied by an increase in markers of systemic inflammation, a violation of the detoxification function of the liver, caused by both direct viral damage to hepatocytes and an increased iatrogenic load on the hepatobiliary system due to polypharmacy. AIM. Studying the use of the drug Laennec in the rehabilitation period as a hepatoprotector and immunomodulator in patients with post-COVID syndrome. MATERIALS AND METHODS. The study included 40 patients with post-COVID syndrome aged 30 to 60 years, with steatosis and steatohepatitis (increased levels of liver transaminases). The clinical effectiveness of Laennec was assessed based on the dynamics of pro-inflammatory biomarkers, liver metabolism indicators, as well as functional tests and psychological questionnaires. RESULTS. The inclusion of Laennec in the rehabilitation program for patients with post-COVID syndrome leads to a more pronounced improvement in lipid metabolism parameters, correction of liver metabolism parameters, a decrease in the level of pro-inflammatory biomarkers, and an improvement in the quality of life of patients than in the control group. DISCUSSION. Significantly significant positive dynamics in the severity of complaints of general weakness and sleep disturbance, as well as indicators of memory impairment and impaired concentration in the main group could indicate the achievement of anabolic, neurotrophic and bioenergetic effects of the Laennec drug. A significantly significant decrease in the level of liver transaminases in the main group indicates the hepatoprotective effect of the drug Laennec, due to the amino acids, vitamins and microelements included in the drug, which support the reactions of phases 1 and 2 of liver detoxification. Normalization of elevated pro-inflammatory markers (ferritin, IL-6, CRP) in patients of the main group may indicate the presence of anti-inflammatory and immunoregulatory effects of the Laennec drug. CONCLUSIONS. A course prescription of the drug Laennec for the purpose of correcting pro-inflammatory markers and hepatoprotection can be recommended for use in complex non-drug rehabilitation to increase its clinical effectiveness, as well as improve subjective indicators of the quality of life of patients with post-COVID syndrome.